Comparison of 8-Hydroxy-Deoxyguanosine Levels in Cervical Cancer Advanced Stages Before and After Chemotherapy - Sardina,; Rauf, Syahrul; Previana Amiruddin, Rina; Nur Asni, Siti; Tadjuddin, Maisuri; Arifuddin, Sharvianty (International Journal of Psychosocial Rehabilitation, 2020)
Cervical cancer is the most commonly diagnosed cancer and the third leading cause of death of women in poor and developing countries. 8-hydroxy-deoxyguanosine (8-OHdG) levels have been widely used as a biomarker of oxidative DNA damage, including cervical cancer. This study aims to compare levels of 8-hydroxy-deoxyguanosine (8-OHdG) as a marker of oxidative stress in advanced cervical cancer (FIGO stages) before and after chemotherapy. This prospective study involved 18 patients stage IIB, 8 patients stage IIIA, 9 patients stage IIIB, and 2 patients stage IIIC of cervical cancer. 8-OHdG levels were measured with the ELISA method. The mean level of 8-OHdG before chemotherapy in stage II was 8.14±9.14 ng/ml and in stage III 8.07±8.79 ng/ml, whereas the mean level of 8-OHdG after chemotherapy in stage II was 24.24±12.46 ng/ml and at stage III 24.67±13.85 ng/ml. 8-OHdG levels increased significantly (p